2020
DOI: 10.1002/lt.25772
|View full text |Cite
|
Sign up to set email alerts
|

Using Artificial Intelligence for Predicting Survival of Individual Grafts in Liver Transplantation: A Systematic Review

Abstract: Background:The demand for liver transplantation far outstrips the supply of deceased donor organs, and so listing and allocation decisions aim to maximise utility. Most existing methods for predicting transplant outcomes utilise basic methods such as regression modellingnewer artificial intelligence techniques have the potential to improve predictive accuracy. Aims:To systematically review studies predicting graft outcomes following deceased liver transplantation using Artificial Intelligence (AI) techniques a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…We further note that not all studies compare the AI tools they have developed to the status quo "non-AI tool" (e.g. MELD or SOFT scores) (12). Even so, evaluating accuracy, sensitivity, specificity, the Receiver Operator Curve (ROC) AUC, etc., will only provide insight to how well an AI makes decisions against retrospective data.…”
Section: Accuracy and Effectiveness Measures Reportedmentioning
confidence: 99%
“…We further note that not all studies compare the AI tools they have developed to the status quo "non-AI tool" (e.g. MELD or SOFT scores) (12). Even so, evaluating accuracy, sensitivity, specificity, the Receiver Operator Curve (ROC) AUC, etc., will only provide insight to how well an AI makes decisions against retrospective data.…”
Section: Accuracy and Effectiveness Measures Reportedmentioning
confidence: 99%
“…They found 2 studies that directly compared machine learning techniques with liver scoring modalities (ie, DRI, SOFT, and BAR) for liver graft outcome. 55 One of the studies was done by Briceño et al who showed the machine learning AUROC of 0.82 was superior to compared with a BAR of 0.62 and a SOFT of 0.57. 56 The other research by Lau et al showed that a random forest and artificial neural network model revealed an AUROC of 0.84 compared with a DRI of 0.68 and SOFT of 0.64.…”
Section: Predictors Of Outcomementioning
confidence: 99%
“…Cardiovascular adverse effects are common with terlipressin and need to be monitored strictly. • Artificial intelligence and risk prediction: Wingfield et al 55 A systematic review of artificial intelligence computing techniques used in liver transplantation to predict individual patient graft survival. They found 2 studies suggesting the superiority of machine learning techniques to standard liver scoring modalities for liver graft outcome.…”
Section: Machine Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…These endpoints must be measured in prospective trials. Research has highlighted promise of AI across gastroenterology, from analysing liver ultrasound images 5 to prognosticating in hepatocellular carcinoma, 6 and from personalising pancreatic cancer management 7 to predicting liver transplantation survival 8 . However, the impact of incorporating such algorithms into clinical workflows has not yet been robustly assessed 9 .…”
mentioning
confidence: 99%